2020
DOI: 10.3390/ijerph17228496
|View full text |Cite
|
Sign up to set email alerts
|

Physical Exercise as a Multimodal Tool for COVID-19: Could It Be Used as a Preventive Strategy?

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) or coronavirus disease 2019 (COVID-19) is a novel coronavirus not previously recognized in humans until late 2019. On 31 December 2019, a cluster of cases of pneumonia of unspecified etiology was reported to the World Health Organization in China. The availability of adequate SARS-CoV-2 drugs is also limited, and the efficacy and safety of these drugs for COVID-2019 pneumonia patients need to be assessed by further clinical trials. For these reas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 78 publications
1
53
0
7
Order By: Relevance
“…In athletes, strenuous exercise (elite competitive sport) has been associated with changes in cytokine production, specifically with increases in plasma concentrations of IL-1, IL-6 and TNF-a to supra-physiological levels (3,72). The functional and potentially clinical significance of competitive sport-induced alterations in inflammatory cytokines results in generalized inflammation of the body, tissue damage, myalgia, alteration of the immune system (susceptibility to infection), fever, and chronic fatigue (73).…”
Section: Am3 and Cytokinesmentioning
confidence: 99%
See 1 more Smart Citation
“…In athletes, strenuous exercise (elite competitive sport) has been associated with changes in cytokine production, specifically with increases in plasma concentrations of IL-1, IL-6 and TNF-a to supra-physiological levels (3,72). The functional and potentially clinical significance of competitive sport-induced alterations in inflammatory cytokines results in generalized inflammation of the body, tissue damage, myalgia, alteration of the immune system (susceptibility to infection), fever, and chronic fatigue (73).…”
Section: Am3 and Cytokinesmentioning
confidence: 99%
“…SARS-CoV-2 infection causes a wide range of symptoms. While a sizable number of patients present flu-like symptoms, others develop a severe condition associated with respiratory distress and pneumonia (3). These cases are also characterized by Acute Respiratory Distress Syndrome (ARDS), renal failure, septic shock or multi-organ failure, conditions that generally require hospitalization, intensive care unit (ICU) admission, and/or mechanical ventilation (4) and a multisystem inflammatory syndrome (5).…”
Section: Introductionmentioning
confidence: 99%
“…Actually, in a recent review, authors concluded that PA has been proven an effective therapy for most chronic diseases, including COVID-19. Consequently, PA could be helpful to regulate physiological systems, such as the inflammatory response and antioxidant defence (Fernández-Lázaro et al, 2020). Indeed, following a respiratory pathology such as COVID-19, there is a drastic reduction in physical strength and fitness, and physical rehabilitation interventions are required to promote recovery post infection (Rooney et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A explicação está relacionada ao aumento do débito cardíaco e do fluxo sanguíneo que interagem de forma mecânica com o endotélio e aumentam a concentração de leucócitos circulantes na corrente sanguínea (Damiot, Pinto, Turner & Gualano, 2020;Silveira et al, 2021). Ressalta-se, ainda, que as imunidades inatas e adaptativas são afetadas positivamente pelo exercício físico, conferindo maior proteção contra infecções, inclusive as virais; ademais, a imunidade humoral também é afetada promovendo maior resposta à vacinação (Renasinghe, Ozemek & Arena, 2020;Fernández-Lázaro et al, 2020) e, o exercício físico, se realizado por mais de seis meses, previne a disfunção imunológica relacionada à senescência e à inflamação crônica, o que pode significar um provável fator protetor contra as complicações decorrentes da COVID-19 (Renasinghe, Ozemek & Arena, 2020;Damiot, Pinto, Turner & Gualano, 2020).…”
Section: Discussionunclassified
“…Outros estudos, os quais relacionaram o exercício aeróbico e a SARS-CoV-2, revelaram que o aumento da capacidade aeróbia pode fortalecer a imunidade à medida que estimula a função das células imunológicas, neutraliza a ansiedade e a depressão, aumenta a elasticidade e força pulmonar e ainda minimiza os fatores de risco desse vírus (Mohamed & Alawna, 2020), já que a Sars-CoV-2 permite a ativação e a liberação de citocinas inflamatórias, como IL-6, proteína C reativa (PCR) e dímero D; além de causar disfunção endotelial, levando à diminuição da produção de óxido nítrico-sintase endotelial (eNOS) e, consequentemente, do óxido nítrico (NO). De forma que a prática de atividade física frequente pode minimizar tais efeitos inflamatórios do vírus, provavelmente, porque reestabelece a liberação de NO, diminuindo, assim, a disfunção endotelial e favorecendo a vasodilatação pulmonar (Nigro et al, 2020;Fernández-Lázaro et al, 2020).…”
Section: Discussionunclassified